Entrepreneurship Learning Model Creates New Entrepreneurs “Merdeka Belajar Kampus Merdeka” in the University - Suranto Suranto; Siti Nurlaela; Adcharina Pratiwi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
This study aims to develop a goodness of fit entrepreneurial learning model and test the found models. The benefit of this research is to develop an entrepreneurial learning model that is able to improve the business mental independence based on their talents. Methods of data collection were carried out through observation, questionnaires and literature study. The research object was UMS Industrial Engineering students. The data analysis method used is validity and reliability test, confirmatory analysis test, student test to see the difference before and after treatment to get entrepreneurial learning model. This development research uses one shot case study experiment with a quantitative approach. The students receive guidance, mentoring, counseling and empowerment in developing entrepreneurial learning models.